Vitreous Olink proteomics reveals inflammatory biomarkers for diagnosis and prognosis of traumatic proliferative vitreoretinopathy - Guo, Haixia; Wang, Tian; Yu, Jinguo; Shi, Zhemin; Liang, Minghui; Chen, Siyue; He, Tiangeng; Yan, Hua (Frontiers in Immunology, 2024)
Backgrounds: To identify inflammatory biomarkers in traumatic proliferative vitreoretinopathy (TPVR) patients and further validate the expression curve of particular biomarkers in the rabbit TPVR model.The Olink-Inflammation-Panel was used to compare the differentially expressed proteins (DEPs) in the vitreous of TPVR patients 7-14 days after open globe injury (OGI) (N=19) and macular hole patients (N=22), followed by correlation analysis between DEPs and clinical signs, protein-protein interaction (PPI) analysis, the areas under the receiver operating characteristic curves (AUCs) analysis and function enrichment analysis. A TPVR rabbit model was established and expression levels of candidate interleukin family members (IL-6, IL-7, IL-33) were measured by enzyme linked immunosorbent assay (ELISA) at 0, 1, 3, 7, 10, 14, 28 days after OGI.Results: Forty-eight DEPs were detected between the two groups. Correlation analysis showed that CXCL5, EN-RAGE, IL-7, ADA, CD5, CCL25, CASP8, TWEAK and IL-33 were significantly correlated with clinical signs including ocular wound characteristics, PVR scoring, PVR recurrence and final visual acuity (R=0.467-0.699, P<0.05), and all with optimal AUC values (0.7344-1).Correlations between DEPs analysis and PPI analysis further verified that IL-6, IL-7, IL-8, IL-33, HGF and CXCL5 were highly interactive (combined score: 0.669-0.983). These DEPs were enriched in novel pathways such as cancer signaling pathway (N=14, P<0.000). Vitreous levels of IL-6, IL-7 and IL-33 in the rabbit TPVR model displayed consistency with the trend in Olink data, all exhibiting marked differential expression 1 day following the OGI.Conclusion: IL-7, IL-33, EN-RAGE, TWEAK, CXCL5, CD5 may be potential biomarkers for TPVR pathogenesis and prognosis, and early post-injury may be an ideal time for TPVR intervention targeting interleukin family biomarkers.